Acinetobacter baumannii-induced ecthyma gangrenosum: case report and review of non pseudomonal cases reported in the literature. - Charaniya, A.L.; Shilpashree, P.; Kavya, H.R. (European Journal of Pediatric Dermatology, 2022)
Ecthyma gangrenosum (EG) is a rapidly progressing cutaneous infection associated with Pseudomonas aeruginosa (PA) septicemia that was previously thought to affect only immunosuppressed individuals. The infection is currently also found in immunocompetent patients and can be caused by other bacteria such as Escherichia coli, Citrobacter freundii, Klebsiella pneumoniae just to name a few. EG due to other bacteria is clinically indistinguishable from PA-induced ecthyma gangrenosum, which is characterized by hemorrhagic blisters rapidly evolving into large necrotic ulcers with significant mortality due to the associated septicemia. Herein we report a case of community acquired ecthyma gangrenosum caused by Acinetobacter baumannii in a child with burns, which was resistant to multiple antibiotics.